Firms, Jobs, and Employment in Moldova - Rutkowski, Jan (World Bank, Washington, D.C., 2013)
Despite low open unemployment, labor market outcomes are unsatisfactory in Moldova. Employment is low and job opportunities are scarce. The author examines labor market performance in Moldova by focusing on firm dynamics. He finds that the low level of employment in Moldova is due to the low rate of firm entry and the low rate of job creation in existing firms. Although the rate of job destruction is high, this is typical of transition economies, and is a problem only because it is not coupled with a commensurate rate of job creation. Firm exit is limited and thus is not an important factor behind job losses. The only sector of the economy that creates jobs on a net basis is that consisting of de novo private and small firms. However, in Moldova this sector is significantly smaller than in the most successful transition economies. The author argues that the primary factor behind the small size of the employment generating sector is the high cost of doing business in Moldova. These include numerous administrative barriers, intrusive and costly inspections, and associated corruption. These costs-extremely high even by regional standards-lower the expected returns to business activity and thus discourage firm formation and growth. The author hence recommends improvements in the investment climate as a primary policy aimed at increasing productive employment and lowering unemployment. Priority should be given to fostering job creation through facilitating the formation of new firms and to reducing the constraints on the expansion of existing firms. The government should avoid measures aimed at forestalling the destruction of unviable jobs and firm exit as these are not conducive to long-run productivity and employment growth. Enhancing labor market flexibility is a further priority, as currently the apparently stringent provisions of the Labor Code are not complied with and enforced. Given the unsatisfactory business environment, active labor market programs are unlikely to be effective unless carefully targeted at the most disadvantaged worker groups.